The expression of dominant negative TCF7L2 in pancreatic beta cells during the embryonic stage causes impaired glucose homeostasis - Weijuan Shao; Xiaoquan Xiong; Wilfred Ip; Fenghao Xu; Zhuolun Song; Kejing Zeng; Marcela Hernandez; Tao Liang; Jianping Weng; Herbert Gaisano; M. Cristina Nostro; Tianru Jin (Elsevier, 2015)
Objective: Disruption of TCF7L2 in mouse pancreatic β-cells has generated different outcomes in several investigations. Here we aim to clarify role of β-cell TCF7L2 and Wnt signaling using a functional-knockdown approach. Methods: Adenovirus-mediated dominant negative TCF7L2 (TCF7L2DN) expression was conducted in Ins-1 cells. The fusion gene in which TCF7L2DN expression is driven by PTRE3G was utilized to generate the transgenic mouse line TCF7L2DNTet. The double transgenic line was created by mating TCF7L2DNTet with Ins2-rtTA, designated as βTCFDN. β-cell specific TCF7L2DN expression was induced in βTCFDN by doxycycline feeding. Results: TCF7L2DN expression in Ins-1 cells reduced GSIS, cell proliferation and expression of a battery of genes including incretin receptors and β-cell transcription factors. Inducing TCF7L2DN expression in βTCFDN during adulthood or immediately after weaning generated no or very modest metabolic defect, while its expression during embryonic development by doxycycline feeding in pregnant mothers resulted in significant glucose intolerance associated with altered β-cell gene expression and reduced β-cell mass. Conclusions: Our observations support a cell autonomous role for TCF7L2 in pancreatic β-cells suggested by most, though not all, investigations. βTCFDN is a novel model for further exploring the role of TCF7L2 in β-cell genesis and metabolic homeostasis.